PROBLEMATIKA PENGELOLAAN PEMBIAYAAN PENDIDIKAN DI INDONESIA: SYSTEMATIC LITERATURE REVIEW TERHADAP EFEKTIVITAS, TRANSPARANSI, DAN AKUNTABILITAS PENGGUNAAN DANA PENDIDIKAN - Pranisma Salsa Imeldania; Dwi Cahyaningdyah; S Martono (STKIP Subang, 2026)
Education financing management is an essential component in improving the quality of education. However, the availability of funds does not necessarily ensure better educational outcomes if the management of financial resources is not carried out effectively, transparently, and accountably. This study aims to analyze the problems of education financing management in Indonesia based on the aspects of funding effectiveness, transparency, and accountability. This research employed a Systematic Literature Review (SLR) method using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. The data were obtained from 15 scientific articles published in national journals between 2022 and 2026 through Google Scholar searches. The articles were analyzed using thematic analysis to identify recurring issues in education financing management. The results show that education financing problems in Indonesia are not only related to funding availability but also to the quality of financial governance. The main issues include budgeting that is not fully based on institutional needs, fund utilization that tends to focus on administrative aspects, limited transparency in financial information disclosure, and accountability practices that are still focused on administrative reporting rather than measuring the impact of fund utilization. Therefore, effective education financing management requires strengthening financial governance to ensure that educational funds can optimally support the improvement of education quality.